Blended learning in Malaysia: a case study of lecturers' readiness at Institut Profesional Baitulmal / Zarina Abdul Aziz - Abdul Aziz, Zarina (2015)
The integration of advantages of face-to-face based format with, e-Learning enables arranging education in a form of so called Blended Learning (BL) which combines the traditional face to face study and online learning. However, studies have shown that there are many potential obstacles which may hinder the effectiveness of lecturers' participation toward blended learning approach. Previous studies have found that most of the attitudes held by academicians were negative, primarily because they doubted the quality of the education that students received through online course. This study will be carried out at a private educational institution with aims to statistically identify how the lecturers' personality traits of technology readiness influence their perceptions toward blended learning and to assess their attitude toward blended learning approach in their teaching activities. Quantitative approach and questionnaire instruments are used to gather the data from the respondents. The findings show that there are significant relationship between technology readiness dimensions with perceived ease of use and perceived usefulness and the lecturers have the positive attitude toward blended learning approach. This study would provide the awareness to the top management about the attitude and perceptions among lecturers towards blended learning approach and the lecturers will have basic exposure on what is basically blended learning is by sharing the outcome of the study during workshop or seminars organized by the institution.